Metabolic Effects on Mouse Embryonic Stem Cells and the Canonical Mammalian Target of Rapamycin Pathway - Bibiana Correia; Maria Inês Sousa; João Ramalho-Santos (BioChem, 2023)
Diapause-like features can be extended to naïve mouse embryonic stem cells (mESCs) to induce paused pluripotency by using INK128 (mTi), a mammalian target of rapamycin (mTOR) inhibitor. As a core integrative pathway, mTOR senses diverse stimuli and translates these cues to coordinate several processes. We have previously shown that the withdrawal of leucine and arginine from the culture medium of naïve mESCs can induce features of a paused-pluripotent state, including reduced cell proliferation, cell cycle arrest, and reductions in glycolytic and oxidative metabolism. However, surprisingly, although mTi did indeed provoke a paused-like state, this was distinct from and less pronounced than what resulted from leucine and arginine removal, and, according to our results, these features did not seem to necessarily be mTOR-driven. Therefore, this possibility should be considered in further experiments, and mTOR inhibition when using INK128 should always be confirmed and not merely assumed when INK128 is present in the culture medium.